UNDERSTANDING FIGURATIVE LANGUAGE IN A LITERARY WORK THROUGH LITERATURE CIRCLE - Putra, Oka Rodi; Devi, Puspita (Borneo Journal of English Language Education, 2019)
This article is launched based on the highly seriously significant problems that are faced by the students in literature class. They are dealing with students’ interest and motivation in learning literature. Most of students are uninterested in and unmotivated to learn about literature since they find difficulties in understanding figurative language. In fact, students do not get the point on how the figurative language is used to illustrate the implied meaning of the passage. Understanding figurative language can be perfectly retrieved through a cooperative learning, that is, literature circles. Literature circles is a temporary discussion groups between students who have chosen to read the same book in which each of the students has their own roles that differ from one another. When students are given a voice in what they read, they are more likely to learn and enjoy the experience. Additionally, their learning deepens their knowledge and becomes more meaningful to them.